The evaluation of the malnutrition in hospitalized infants - Sinem Akbay Ak; Oya Baltalı; Özkan İlhan; Sezin Akman (Northwestern Medical Journal)
Aim: Malnutrition is a state of inadequate nutrition that can be prevented or treated with appropriate nutrition. The aim of this study is to determine the nutritional status of hospitalized infants and to establish the relationship between anthropometric measurements and malnutrition with underlying acute or chronic diseases.